Overview of Major Industries in Bangladesh (Journal of Chemical Engineering, 2017)
Industrialization is an essential prerequisite for rapid economic growth of a developing country like Bangladesh. This study shows the major industrial growth of the country and their impact on the national economic development, public safety, health and environment. The capacity, productivity and export/import values of industrial products are used to establish the baseline scenario. There are significant numbers of chemical intensive industries such as textile, leather, food, fertilizer and pharmaceutical industry that have direct impact on socio economic development of the country. It is worth noting that Bangladesh is not only importing industrial products from other countries but also exporting a substantial amount of product to over 100 countries of the world and shows an impressive growth in industrial sectors Rapid industrial growth often offers a huge burden of environmental pollution and associated risks. Thus, there are still lots of space for Bangladesh to flourish in this sector. This study presents the prospects, and recommendations for major industrial sectors to achieve safe and sustainable industrial growth in Bangladesh.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 51-58